Comparative and phylogenetic analysis of chloroplast genomes from ten species in Quercus section Cyclobalanopsis - Huang, Ke; Li, Buyu; Chen, Xiaoli; Qin, Chun; Zhang, Xuemei (Frontiers in Plant Science, 2024)
The genus Quercus L. is widely acknowledged as a significant assemblage within East Asia tropical and subtropical broadleaf evergreen forests, possessing considerable economic importance. Nevertheless, the differentiation of Quercus species is deemed arduous, and the interrelations among these species remain enigmatic. Leveraging Illumina sequencing, we undertook the sequencing and assembly of the chloroplast (cp) genomes of seven species belonging to Quercus section Cyclobalanopsis (Quercus argyrotricha, Q. augustinii, Q. bambusifolia, Q. bella, Q. edithiae, Q. jenseniana, and Q. poilanei). Furthermore, we collated three previously published cp genome sequences of Cyclobalanopsis species (Q. litseoides, Q. obovatifolia, and Q. saravanensis). Our primary objective was to conduct comparative genomics and phylogenetic analyses of the complete cp genomes of ten species from Quercus section Cyclobalanopsis. This investigation unveiled that Quercus species feature a characteristic circular tetrad structure, with genome sizes ranging from 160,707 to 160,999 base pairs. The genomic configuration, GC content, and boundaries of inverted repeats/single copy regions exhibited marked conservation. Notably, four highly variable hotspots were identified in the comparative analysis, namely trnK-rps16, psbC-trnS, rbcL-accD, and ycf1. Furthermore, three genes (atpF, rpoC1, and ycf2) displayed signals of positive selection pressure. Phylogenetic scrutiny revealed that the four sections of Cyclobalanopsis clustered together as sister taxa. The branch support values ranged from moderate to high, with most nodes garnering 100% support, underscoring the utility of cp genomic data in elucidating the relationships within the genus. Divergence time analysis revealed that Section Cyclobalanopsis represents the earliest type of Quercus genus. The outcomes of this investigation establish a foundation for forthcoming research endeavors in taxonomy and phylogenetics.